Isotretinoin-induced dermographism and urticaria: A rare cutaneous hypersensitivity reaction (Indian Journal of Case Reports, 2025)
Isotretinoin is a systemic retinoid extensively used for intense pimples, with not unusual, place-damaging results like mucocutaneous dryness being well-documented. This record highlights an extraordinary case of isotretinoin-triggered dermographism and urticaria. A 27-year-old girl on 20 mg/day of oral isotretinoin for intense pimples developed chronic pruritus, linear erythematous streaks, and urticarial plaques on her lower limbs after 4 weeks. With no records of allergies, a likely damaging drug response became recognized through the usage of the Naranjo evaluation tool. Isotretinoin was discontinued, and the affected person was treated with oral bilastine and tapered methylprednisolone, attaining complete healing within 10 days. This case underscores the significance of spotting odd cutaneous reactions to isotretinoin to ensure the protection of affected person and beautify pharmacovigilance.